2017
DOI: 10.1111/imm.12747
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lymph node CD11b CD103+ PD‐L1High dendritic cells highly induce regulatory T cells

Abstract: Dendritic cells (DCs) in mesenteric lymph nodes (MLNs) induce Foxp3 regulatory T cells to regulate immune responses to beneficial or non-harmful agents in the intestine, such as commensal bacteria and foods. Several studies in MLN DCs have revealed that the CD103 DC subset highly induces regulatory T cells, and another study has reported that MLN DCs from programmed death ligand 1 (PD-L1) -deficient mice could not induce regulatory T cells. Hence, the present study investigated the expression of these molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 56 publications
1
40
1
2
Order By: Relevance
“…Of note, lentiviral transduction and LPS activation associated expression of secreted factors and cell surface molecules by ligand overexpressing DCs could contribute to modulation of T cell properties differently than that by APC subsets that naturally express elevated levels of these ligands. This is evident from our observation, in contrary to previous reports21,[49][50][51][52][53][54] , PD-L1 overexpressing engineered DCs do not induce an increase in Foxp3+ T cells, but these DCs suppress both Th1 and Th17 (IFNγ and IL17) responses. Nevertheless, the overall impact of engineered mono-and multi-ligand DCs on T cell function, as anticipated with enhanced engagement of T cell repressor receptors, is hyporesponsiveness/tolerance.…”
contrasting
confidence: 99%
“…Of note, lentiviral transduction and LPS activation associated expression of secreted factors and cell surface molecules by ligand overexpressing DCs could contribute to modulation of T cell properties differently than that by APC subsets that naturally express elevated levels of these ligands. This is evident from our observation, in contrary to previous reports21,[49][50][51][52][53][54] , PD-L1 overexpressing engineered DCs do not induce an increase in Foxp3+ T cells, but these DCs suppress both Th1 and Th17 (IFNγ and IL17) responses. Nevertheless, the overall impact of engineered mono-and multi-ligand DCs on T cell function, as anticipated with enhanced engagement of T cell repressor receptors, is hyporesponsiveness/tolerance.…”
contrasting
confidence: 99%
“…Several recent manuscripts suggest a potentially important role for ALDH in immunity. This research has focused on the role of ALDH in Treg induction, function and resistance to cytotoxic therapy . The gastrointestinal tract, pulmonary tract and skin are the main organ systems that have been identified in which Treg cell activity is enhanced through ALDH (Fig.…”
Section: Aldh In Treg Induction and Functionmentioning
confidence: 99%
“…In short, an immunological stimulus leads to, among other things, up‐regulation of ALDH in multiple cells . RA produced from ALDH then enhances Treg induction and function from naive CD4 + T cells . These antigen‐specific Treg cells then function to promote immune tolerance (Fig.…”
Section: Aldh In Treg Induction and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These CD103 + DC subpopulations have been reported to play a key role in tolerance induction in the gut, as they produce high levels of RA and TGFb, which are key mediators of FoxP3 induction in the intestinal microenvironment [41,42]. In fact, it has been previously shown that CD103 + CD11b À PD-L1 hi DC are high inducers of pTregs [43], in agreement with the reported effect of PD-L1 during Treg conversion from na€ ıve T cells by immature DCs in vitro [44].…”
Section: Resultsmentioning
confidence: 99%